The homeostatic and circadian sleep recovery responses after total sleep deprivation in mice. (20th April 2017) - Dispersyn, Garance; Sauvet, Fabien; Gomez‐Merino, Danielle; Ciret, Sylvain; Drogou, Catherine; Leger, Damien; Gallopin, Thierry; Chennaoui, Mounir
Summary: Many studies on sleep deprivation effects lack data regarding the recovery period. We investigated the 2‐day homeostatic and circadian sleep recovery response to 24 h of total sleep deprivation (TSD) induced by brief rotation of an activity wheel. Eight mice were implanted with telemetry transmitters (DSI F40‐EET) that recorded simultaneously their electroencephalography (EEG), locomotor activity and temperature during 24 h of baseline (BSL), TSD and 2 days of recovery (D1 and D2). In a second experiment, two groups of five non‐implanted mice underwent TSD or ad libitum sleep, after which they were killed, adrenal glands were weighed and blood was collected for analysis of corticosterone concentration. During TSD mice were awake at least 97% of the time, with a consecutive sleep rebound during D1 that persisted during D2. This was characterized by increases of non‐rapid eye movement (NREM) sleep (44.2 ± 6.9% for D1 and 43.0 ± 7.7% for D2 versus 33.8 ± 9.2% for BSL) and the relative delta band power (179.2 ± 34.4% for D1 and 81.9 ± 11.2% for D2). Greater NREM and REM sleep amounts were observed during the 'light' periods. Temperature and locomotor activity characteristics were unchanged during D1 and D2 versus BSL. In non‐implanted mice, corticosterone levels as well as adrenal gland and overall body weights did not differ between TSD and ad libitum sleep groups. In conclusion, 24 h of TSD in an activity wheel without stress responses influence homeostatic sleep regulation with no effect on the circadian regulation over at least 2 days of recovery in mice.